NEK7-Mediated Activation of NLRP3 Inflammasome Is Coordinated by Potassium Efflux/Syk/JNK Signaling During Staphylococcus aureus Infection - Liu, Ruiqing; Liu, Yashan; Liu, Chang; Gao, Aijiao; Wang, Lin; Tang, Huixin; Wu, Qiang; Wang, Xia; Tian, Derun; Qi, Zhi; Shen, Yanna (Frontiers in Immunology, 2021)
Staphylococcus aureus (S. aureus) is a foodborne pathogen that causes severe diseases, such as endocarditis, sepsis, and bacteremia. As an important component of innate immune system, the NLR family pyrin domain-containing 3 (NLRP3) inflammasome plays a critical role in defense against pathogen infection. However, the cellular mechanism of NLRP3 inflammasome activation during S. aureus infection remains unknown. In the present study, we found that spleen tyrosine kinase (Syk) and c-Jun N-terminal kinase (JNK) were rapidly phosphorylated during S. aureus infection. Moreover, a Syk/JNK inhibitor and Syk/JNK siRNA not only reduced NLRP3 inflammasome-associated molecule expression at the protein and mRNA levels, apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC) speck formation, and interleukin-1β (IL-1β), and IL-18 release but also rescued the decreased NIMA-related kinase 7 (NEK7) expression level following suppression of the NEK7-NLRP3 interaction in macrophages. Interestingly, Syk/JNK phosphorylation levels and NLRP3 inflammasome-associated molecule expression were decreased by blockade of K+ efflux. Furthermore, activation of the NLRP3 inflammasome and a lower NEK7 protein level were found in vivo upon S. aureus infection. Taken together, our data indicated that S. aureus infection induces a K+ efflux/Syk/JNK/NEK7-NLRP3 signaling pathway and the subsequent activation of the NLRP3 inflammasome for the release of proinflammatory cytokines. This study expands our understanding of the basic molecular mechanism regulating inflammation and provides potential value for anti-infective drug development against S. aureus infection.